2003
DOI: 10.1111/j.1728-4457.2003.00647.x
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Male Excess Mortality: Insights from Cloistered Populations

Abstract: The degree to which biological factors contribute to the existence and the widening of mortality differences by sex remains unclear. To address this question, a mortality analysis for the years 1890 to 1995 was performed comparing mortality data on more than 11,000 Catholic nuns and monks in Bavarian communities living in very nearly identical behavioral and environmental conditions with life table data for the general German population. While the mortality differences between women and men in the general Germ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
107
0
9

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 123 publications
(119 citation statements)
references
References 100 publications
3
107
0
9
Order By: Relevance
“…Since the first life tables were constructed in the mid 18th century it is a well established fact that women, on average, live longer than men (Luy, 2003). While the gender-gap, defined as female excess life expectancy, was first observed in the now developed countries, in the 21st century it is basically a universal phenomenon.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the first life tables were constructed in the mid 18th century it is a well established fact that women, on average, live longer than men (Luy, 2003). While the gender-gap, defined as female excess life expectancy, was first observed in the now developed countries, in the 21st century it is basically a universal phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…Preston and Wang (2006), for example, investigate sex differences in the mortality of smokers and non-smokers and estimate that changes in smoking patterns contributed about 20 % to the declining gender-gap. Luy (2003) compares life expectancy of the cloistered subpopulation in Bavaria with that of the German population at large. For the period 1965 to 1990 he observes that the life expectancy of nuns exceeds that of monks by 2.3 years.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Investigators of the most recent of such reports concluded that "the current excess of female life expectancy in adulthood is a relatively new demographic phenomenon". 2 The divergence and reconvergence of male-female mortality is well known to be largely due to different levels and trends in deaths from external causes (injuries) and from disorders such as lung cancer and cardiovascular diseases, for which risk factors (eg, smoking) have different trends in men and women.…”
mentioning
confidence: 99%
“…Biological determinants alone make the average life expectancy of males shorter than of females by one year to two years (Abdulraheem et al, 2011;Luty, 2003;Ram, 1993). Larger differences are already conditioned by non-biological factors.…”
Section: Change In the Average Life Expectancymentioning
confidence: 99%